Karakteristik Tindakan Asusila di Bawah Umur di Rumah Sakit Bhayangkara Makassar Tahun 2024 - Mansyur, Mauluddin; Mathius, Denny; Assegaf, Zulfikar Gaffar; Paradise, Novia Paramita; Sahabuddin, Shafira; 97, Komando (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Immoral behavior in children and adolescents includes actions that violate prevailing social and moral norms and demonstrate a disregard for ethical principles and societal rules. Complex interactions between genetic, environmental, and social factors influence the development of immoral behavior in children. This study has the main objective to obtain a comprehensive understanding of the characteristics of immoral acts experienced by underage victims who were recorded or treated at the Bhayangkara Hospital Makassar during one year, namely 2024. The approach taken in this study is a descriptive method with a retrospective design, where all data is collected systematically from cases that occurred and were recorded from January to December 2024. There were 192 victims of immoral acts involving children, 98.96% of whom were girls and 1.04% of whom were boys. Victims with an age group of <5 years were 5.73%, 5-12 years 33.33%, 13-17 years 60.94%. Victims of sexual violence in children 10.42% experienced physical violence, and 15.63% experienced verbal violence. The perpetrators were 81.77% of people known to the victim. There were more female victims of violence than male victims. The perpetrators of violence were often people known to the victim.